Calculated rate constants of the chemical reactions involving the main byproducts SO2F, SOF2, SO2F2 of SF6 decomposition in power equipment. (11th March 2016) - Fu, Yuwei; Rong, Mingzhe; Yang, Kang; Yang, Aijun; Wang, Xiaohua; Gao, Qingqing; Liu, Dingxin; Murphy, Anthony B
Abstract: SF6 is widely used in electrical equipment as an insulating gas. In the presence of an electric arc, partial discharge (PD) or spark, SF6 dissociation products (such as SF2, SF3 and SF4 ) react with the unavoidable gas impurities (such as water vapor and oxygen), electrodes and surrounding solid insulation materials, forming several toxic and corrosive byproducts. The main stable decomposition products are SO2 F, SO2 F2 and SOF2, which have been confirmed experimentally to have a direct relationship with discharge faults, and are thus expected to be useful in the fault diagnosis of power equipment. Various studies have been performed of the main SF6 decomposition species and their concentrations under different types of faults. However, most of the experiments focused on the qualitative analysis of the relationship between the stable products and discharge faults. Although some theoretical research on the formation of main SF6 derivatives have been carried out using chemical kinetics models, the basic data (chemical reactions and their rate constants) adopted in the model are inaccurate and incomplete. The complex chemical reactions of SF6 with the impurities are ignored in most cases. The rate constants of some reactions obtained at ambient temperature or in a narrow temperature range are adopted in the models over a far greater range, for example up to 12 000 K, due to the difficulty in the experimental measurement and theoretical estimation of rate coefficients, particularly at high temperatures. Therefore, improved theoretical models require not only the consideration of additional SF6 decomposition reactions in the presence of impurities but also on improved values of rate constants. This paper is devoted to determining the rate constants of the chemical reactions relating to the main byproducts of SF6 decomposition in SF6 gas-insulated power equipment: SO2 F, SOF2 and SO2 F2 . Quantum chemistry calculations with density functional theory, conventional transition state theory and Wigner's tunneling effect correction are employed to estimate the rate constants of four important chemical reactions: F  +  SO2 F  →  SO2 F2, F2   +  SO2   →  SO2 F2, SO2 F  +  SF5   →  SF6   +  SO2 and SOF3   +  SF3   →  SF4   +  SOF2 . The results are derived for a large temperature range, from 300 to 12 000 K, and finally fitted by a three-parameter Arrhenius equation. This work lays a basis for the further study of the SF6 decomposition mechanism by means of chemical kinetics modelling.